A VARIAÇÃO DA DUREZA E DA DENSIDADE DE TRICOMAS DAS FOLHAS DE CORDIA TRICHOTOMA (BORAGINACEAE) E O EFEITO NO DESGASTE DAS MANDÍBULAS DE CISTUDINELLA OBDUCTA (COLEOPTERA, CHRYSOMELIDAE, CASSIDINAE) - NORONHA, ANA P.; MEDEIROS, LENICE (Salão do Conhecimento, 2013)
Resumo